2021
DOI: 10.1111/nph.17812
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin‐like protein CML24 interacts with CAMTA2 and WRKY46 to regulate ALMT1‐dependent Al resistance in Arabidopsis thaliana

Abstract: Summary ALUMINUM‐ACTIVATED MALATE TRANSPORTER1 (ALMT1)‐mediated malate exudation from roots is critical for aluminium (Al) resistance in Arabidopsis. Its upstream molecular signalling regulation is not yet well understood. The role of CALMODULIN‐LIKE24 (CML24) in Al‐inhibited root growth and downstream molecular regulation of ALMT1‐meditaed Al resistance was investigated. CML24 confers Al resistance demonstrated by an increased root‐growth inhibition of the cml24 loss‐of‐function mutant under Al stress. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(28 citation statements)
references
References 69 publications
(122 reference statements)
0
28
0
Order By: Relevance
“…CaM7 is a component of photomorphogenesis and multiple signaling pathways are involved in plant immunity, biotic and abiotic stress responses, and hormonal responses (Basu et al, 2021). On the other hand, CML24 plays important roles in pollen germination and pollen tube extension (Yang et al, 2014), circadian oscillation (Martí Ruiz et al, 2018), root mechanoresponses (Wang et al, 2011), Al resistance (Zhu et al, 2022), as well as seed germination, floral transition, ion stress and the sensing of photoperiod (Delk et al, 2005). CML42 participated in trichome morphology (Dobney et al, 2009), insect herbivory defense and drought stress responses (Vadassery et al, 2012;Scholz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…CaM7 is a component of photomorphogenesis and multiple signaling pathways are involved in plant immunity, biotic and abiotic stress responses, and hormonal responses (Basu et al, 2021). On the other hand, CML24 plays important roles in pollen germination and pollen tube extension (Yang et al, 2014), circadian oscillation (Martí Ruiz et al, 2018), root mechanoresponses (Wang et al, 2011), Al resistance (Zhu et al, 2022), as well as seed germination, floral transition, ion stress and the sensing of photoperiod (Delk et al, 2005). CML42 participated in trichome morphology (Dobney et al, 2009), insect herbivory defense and drought stress responses (Vadassery et al, 2012;Scholz et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In this issue of New Phytologist , Zhu et al . (2022; pp. 2471–2487) found that a calmodulin‐like protein, CML24, is involved in the Ca 2+ signaling that regulates the ALMT1‐mediated secretion of malate from roots by interacting with two transcription factors – CALMODULIN BINDING TRANSPORTER ACTIVATOR 2 (CAMTA2) and WRKY46 in Arabidopsis.
‘The study of CML24 indicates that Ca signaling plays an important role in malate secretion‐mediated Al tolerance.
…”
Section: Figmentioning
confidence: 99%
“…In Arabidopsis, Al tolerance is mainly achieved by secretion of malate from the roots, which is mediated by ALUMINIUM-ACTIVATED MALATE TRANSPORTER 1 (ALMT1) (Hoekenga et al, 2006). In this issue of New Phytologist, Zhu et al (2022; pp. 2471-2487 found that a calmodulin-like protein, CML24, is involved in the Ca 2+ signaling that regulates the ALMT1-mediated secretion of malate from roots by interacting with two transcription factors -CALMODULIN BINDING TRANSPORTER ACTIVATOR 2 (CAMTA2) and WRKY46 in Arabidopsis.…”
mentioning
confidence: 99%
“…Malate transporters (ALMTs) are associated with Al tolerance in plants. The ALMT1 gene, which was the first ALMT family gene discovered in wheat and Arabidopsis ( Arabidopsis thaliana ), encodes an Al-activated transporter that induces malate secretion in the roots and Al tolerance is improved by decreasing the Al ion concentration in cells ( Sasaki et al, 2004 ; Vives-Peris et al, 2020 ; Zhu et al, 2022 ). The Al 3+ -enhanced malate transporter homolog AtALMT1 was subsequently identified in Arabidopsis ( Kobayashi et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%